Model Psikoterapi Zikir dalam Meningkatkan Kesehatan Mental - Daimul Ikhsan; Muhammad Irsyadi Fahmi; Asep Mafan (Academica: Journal of Multidisciplinary Studies, 2017)
This article is structured to examine the Islamic psychotherapy model using zikr with saying "Subhanallah" to improve the mental health of the students. This research uses descriptive qualitative approach by collecting data from observation and interview to student who become santri at the boarding school of Al-Hikmah, Sraten, Gatak, Sukoharjo. The author also conducts the literature review of books and articles which is relevant with the research problem, in order to enrich the discussion. The results of the research indicate that the Islamic psychotherapy model using zikr can create inner peace, therefore it will improve the mental health. The improved inner health is marked by the increased ability of students to receive course materials, can control emotions, and also increased learning achievement. Thus, the model of zikr psychotherapy can be used to improve mental health.Keywords:zikr, psychotherapy, health, mental